Treatment of general paralysis of the insane - Lees, Robert (The University of Edinburgh, 1938)
The History of the Treatment of General Paralysis of the Insane has been outlined - first the recognition of General Paralysis of the Insane as a clinical entity, and its relation to Syphilis, later the pyrexial treatment by malaria and other fevers, then chemo-therapy, and more recently electro-pyro-therapy.

Accurate methods of Diagnosis of General Paralysis of the Insane (including the rare Juvenile form) are discussed.

The Technique of Malaria Therapy is discussed, including the method of inoculation, the choice of the type of malaria, the selection of suitable cases, precautions during the course of the fever and the risks entailed.

A brief outline of the Treatment of General Paralysis of the Insane by anti-syphilitic drugs is given,; but combined treatment with Tryparsamide and Bismuth is preferred.

REVIEW OF CASES PERSONALLY OBSERVED: 180 Cases of General Paralysis of the Insane have been treated in Edinburgh from 1925 - 1938. Records of these cases have been perused.

80 Cases have been observed by the writer over an adequate period of time.

The procedure adopted was a combination of Malaria Treatment and Tryparsamide and Bismuth Therapy.

The results of treatment of 80 Personal Cases are discussed: 40.8% are reported as cured; 26.3%" " " improved; 14.5% " " " stationary; 5.3% " " " worse; 12.5% " " " dead.

A standard is described by which the cases are judged.

The Serological and Cerebrospinal Fluid changes after treatment are reviewed and the results are correlated to the clinical findings.